In the Beginning There Was None: Supreme Court Review of State Criminal Prosecutions - Walsh, Kevin C (2015)
This Article challenges the unquestioned assumption of all contemporary scholars of federal jurisdiction that section 25 of the Judiciary Act of 1789 authorized Supreme Court appellate review of state criminal prosecutions. This Article resurrects Charles Hammond’s arguments and contends that he was right: the best interpretation of section 25 is that it did not encompass Supreme Court appellate review of state criminal prosecutions. Others may reasonably disagree with this Article’s ultimate interpretive conclusion about section 25’s limited reach even while acknowledging the strength of the various supporting arguments. Accordingly, this Article’s basic claim comes in both a strong version and a weak version. The strong version: Section 25’s authorization of Supreme Court appellate review of state court decisions was limited to civil suits and did not extend to criminal prosecutions. The weak version is that the arguments for a civil-only interpretation of section 25 were sufficiently strong at the time of Cohens that the Court permissibly could have dismissed for lack of statutory jurisdiction. This Article proceeds in three parts. Part I sets out the basic arguments from text and context that support a civil-only interpretation of section 25. Part II addresses the strongest objections. And Part III explores the broader significance of the surprising rediscovery of civil-only section 25